Pengaruh Kualitas Produk Mizone Terhadap Kepuasan Konsumen di Masyarakat Bandar Lampung - Tria, Ratu; Amelia, Salsabila; Nurhalizah, Nurhalizah; Sanjaya, Vicky F (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This survey aims to introduce Mizone products to the Bandar Lampung community. Researchers use data collection techniques such as questionnaires and literature reviews to obtain accurate data and information. As a data collection method, questionnaires are used to examine respondents’ opinions using scores and Likert scales that measure the attitudes, opinions, and perceptions of individuals or groups of people toward social phenomena. Additionally, the researchers also used social media such as WhatsApp and Instagram to collect data from a survey sample consisting of students, civilian employees, students, and workers. In this study, researchers also used supporting data from various sources such as books, previous research papers, scientific journals, and other articles to supplement existing information. This will help researchers provide a broader context and theory about Mizon products and the scarcity needs of the people of Bandar Lampung. It is hoped that the results of this study will provide insight into the status of Mizon products in the Bandar Lampung community and support the development of products more suited to the scarce needs of this community. It is also hoped that this research will provide a theoretical basis for Mizone’s future product development. The results show that the variable “Product Quality” has a significant positive impact on consumer satisfaction with the original sample value of 0.779.Survei ini bertujuan untuk memperkenalkan produk Mizone kepada masyarakat Bandar Lampung. Peneliti menggunakan teknik pengumpulan data seperti kuesioner dan tinjauan pustaka untuk memperoleh data dan informasi yang akurat. Sebagai metode pengumpulan data, kuesioner digunakan untuk mengetahui pendapat responden dengan menggunakan skor dan skala likert yang mengukur sikap, pendapat, dan persepsi individu atau kelompok masyarakat terhadap fenomena sosial. Selain itu, peneliti juga menggunakan media sosial seperti WhatsApp dan Instagram untuk mengumpulkan data dari sampel survei yang terdiri dari pelajar, pegawai negeri sipil, pelajar, dan pekerja. Dalam penelitian ini, peneliti juga menggunakan data pendukung dari berbagai sumber seperti buku, makalah penelitian terdahulu, jurnal ilmiah, dan artikel lainnya untuk melengkapi informasi yang ada. Hal ini akan membantu peneliti memberikan konteks dan teori yang lebih luas tentang produk Mizon dan kelangkaan kebutuhan masyarakat Bandar Lampung. Hasil penelitian ini diharapkan dapat memberikan wawasan mengenai status produk Mizon di masyarakat Bandar Lampung dan mendukung pengembangan produk yang lebih sesuai dengan kebutuhan masyarakat yang langka. Penelitian ini juga diharapkan dapat memberikan landasan teori bagi pengembangan produk Mizone di masa depan. Hasil penelitian menunjukkan bahwa variabel “Kualitas Produk” mempunyai pengaruh positif signifikan terhadap kepuasan konsumen dengan nilai original sampel 0. 779.